PdII‐Catalyzed Oxidative Tandem aza‐Wacker/Heck Cyclization for the Construction of Fused 5, 6‐Bicyclic N, O‐Heterocycles. Issue 15 (3rd July 2018) - Ye, Chenghao; Kou, Xuezhen; Xia, Jingzhao; Yang, Guoqiang; Kong, Li; Wei, Quhao; Zhang, Wanbin
Abstract: A Pd II ‐catalyzed oxidative tandem cyclization was developed for the construction of fused 5, 6‐bicyclic N, O‐heterocycles. This reaction was enabled by the combined use of a 3‐methylpyridine ligand and pentafluorobenzoic acid additive. A range of heterocyclic products with different substituents could be prepared in moderate to good yields via this methodology. Several transformations, including a scaled‐up preparation of product 2 a, were also carried out showing the good applicability of our methodology. Abstract : Bicycles : A Pd II ‐catalyzed tandem aza‐Wacker/Heck cyclization was developed for the construction of a range of fused 5, 6‐bicyclic N, O‐heterocycles. This reaction was enabled by the combination of 3‐methylpyridine as a ligand and pentafluorobenzoic as an acidic additive.